Oxidation Resistance of a Co-Base Superalloy Improved by Pre-Oxidation Heat Treatment. Issue 6 (1st January 2016) - Liu, Longfei; Wu, Shusen; Chen, Yang; Lü, Shulin
Abstract : The influence of a pre-existing multi-oxide layer on the subsequent re-oxidation at different temperatures of a 22Co-21Ni-23Fe-29Cr-1.6Si-1Mn superalloy was investigated. The pre-oxidation heat-treatment (PHT) at 1200°C for 5 min resulted in the formation of a protective multi-oxide layer. The behavior of pre-treated and non pre-treated samples during isothermal oxidation at 800, 900 and 1000°C in air was studied. Results showed that rate-constants of the oxidation processes of pre-treated samples were significantly lower than those of the non pre-treated ones. Oxidation at 800, 900 and 1000°C in air for 100 h, resulted in the formation of MnCr2 O4, Cr2 O3 and SiO2 compounds for both kinds of samples. A diffusion-controlled mechanism is proposed to describe the oxidation process.